Una carrera profesional con espacio para la ciencia en la Argentina de la primera mitad del siglo XX : Angel Roffo y la cancerología experimental - Buschini, José (Quipu.)
This article analyses the professional career of the argentinian physician Angel Roffo, with emphasis on its scientific aspects. It considers the relation between the selection of cancer as his main subject of study (a disease that was gaining its moment among the local physicians and state functionaries) and the consolidation of a succesful professional strategy which included scientific research, in a context where those activities were not clearly institutionalized within local universities and lacked support from the state. It also studies the double character of Roffo?s professional identity, which combined scientific research and activities relating the organization of the fight against cancer in Argentina.